RISK-BASED CONTRIBUTION IN DEPOSIT GUARANTEE SCHEMES: A ROBUST PRINCIPAL COMPONENT ANALYSIS IN KEY RISK FACTORS’ WEIGHTING STEP - SAVERIO GIORGIO; PINA MURÈ; COSIMO PACCIONE; LUCILLA BITTUCCI (Journal of Financial Management, Markets and Institutions, 2024)
This paper investigates the method for calculating funding banks must provide to Deposit Guarantee Schemes (DGSs) according to the “ex-ante” and “risk-based” criteria introduced by Directive 2014/49/EU (DGSD). We aim to further support the existing documents providing an approach to identify risk indicators and assign weights thereof to determine fundings to be paid to DGSs. It is worth noting that such an approach could enhance current practices as it takes into account the risk and performance of banks as opposed to the overall banking market. By doing so, a more targeted funding can be encouraged. Our results consider the Texas ratio as one of the indicators to look out for. Likewise, such methods could serve as self-assessment frameworks for Institutional Protection Schemes (IPSs) and banks, fostering sound and prudent management, in turn warding off “moral hazard” issues.